Understanding the knowledge and engagement of facilities management with dementia-friendly design in Irish hospitals: an exploratory study. Issue 9 (11th January 2021) - Xidous, Dimitra; Grey, Tom; Kennelly, Sean P.; O'Neill, Desmond
Abstract : Purpose: This exploratory study stems from research conducted between 2015–2018 focussing on dementia-friendly design (DFD) in hospitals (Grey T. et al. 2018). Specifically, this study focusses on facilities management (FM) staff in Irish hospitals to gain a preliminary understanding of the level of knowledge and engagement of FM in the implementation of dementia-friendly hospital (DFH) design. Design/methodology/approach: A mixed-methods approach based on a series of ad hoc semi-structured interviews, and an online survey. The aims were, namely, assess the extent of FM engagement in hospital works; measure the level of awareness regarding DFD; and identify facilitators and barriers to DFD in hospital settings. Participants (74) comprised FM staff in 35 Irish acute care hospitals. The research findings are based on thematic analysis of ad hoc semi-structured interviews (participants, n = 4) and survey responses (participants, n = 13). Findings: While FM staff reported to possess important knowledge for building DFH, they also mentioned a lack of engagement of FM in design processes and hospital works. Practical implications: The research has gained insight into the role of FM in promoting a dementia-friendly approach. Lack of or poor engagement of FM in design processes and hospital works means not fully tapping into rich expertise that would be invaluable in the development, implementation and maintenance of DFH. Universal design is a key driver for facilitating their engagement in the design, implementation and maintenance of DFH environments. Originality/value: This is the first study exploring the role of FM in supporting a DFD approach in acute care hospitals.